“THE ARTISTIC REPRESENTATION OF DAILY LIFE IN VILLAGE COURTYARDS: INSIGHTS FROM WORLD GENRE PAINTING” - Alimova Dinara Namozovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the depiction of daily life in village courtyards as presented in world genre painting. The study analyzes how artists portray everyday activities, family interactions, and the surrounding natural environment through composition, color, and light. By examining the works of renowned European and Russian artists, the article demonstrates that village courtyard scenes serve both aesthetic and cultural purposes. These paintings reflect social norms, historical contexts, and human relationships with nature, providing valuable insight into rural life across different periods and regions.